Optimisme Dan Husnuzhan Kepada Allah Perspektif Psikologi Pendidikan Islam - Dika Syam El-Fatony; Muhammad Akmansyah (Al-Kindi, 2025)
This article discusses optimism and husnuzhan (positive thinking toward Allah) as a psychological foundation in Islamic education. The phenomenon of a psychological crisis among the younger generation such as increasing anxiety, pessimism, and the loss of life’s meaning serves as the background for highlighting the importance of this theme. The Qudsi Hadith, “I am as My servant thinks of Me” (Narrated by Bukhari & Muslim), is used as an epistemological basis that connects Islamic spirituality with educational psychology. The research method employed is library research with content analysis of classical Islamic texts, contemporary literature, and related studies. The results of the study yield a literature-based framework of Islamic Educational Psychology consisting of three main dimensions: (1) theological (belief in Allah’s mercy), (2) psychological (optimism, resilience, and self-efficacy), and (3) educational (spirituality-based learning strategies). This article asserts that optimism and husnuzhan are not merely moral values, but psychological strengths capable of strengthening students’ mental resilience and learning motivation. These findings are expected to enrich the field of Islamic Educational Psychology and open opportunities for further empirical and applicative research.